2021
DOI: 10.3390/geosciences11070267
|View full text |Cite
|
Sign up to set email alerts
|

Elinor Wight Gardner: Pioneer Geoarcheologist, Quaternary Scientist and Geomorphologist

Abstract: Elinor Wight Gardner (1892–1981) was the first female geologist who worked and published as a geoarcheologist. During her career, she worked in arid lands of North Africa, Mediterranean and the Near East, and was regarded as a pioneering geoscientist who made important contributions in multiple fields, including archeology, geomorphology, paleontology and Quaternary science. Despite her ground-breaking work at many archeological sites, Gardner’s impact has been largely unrecognized. Few details are known about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Brass, 2018; Clarke et al, 2016; Gasse, 2000; Gatto and Zerboni, 2015; López-García et al, 2013; Mercuri et al, 2022; Nicoll, 2004; Ritchie and Haynes, 1987). In arid lands, scholars documented the occurrence, within in the geological record, of pedosedimentary features that are incompatible with present-day dryland climates and environs (Cremaschi et al, 2010; Nicoll et al, 2021). Because such natural contexts were often found intimately mixed with archaeological remains, it quickly became clear that the very nature of human settlements, migrations and achievements throughout the archaeological past needed to be – at least partially – scrutinized through the lens of physical geography and environmental changes (Butzer, 1982; Heitz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Brass, 2018; Clarke et al, 2016; Gasse, 2000; Gatto and Zerboni, 2015; López-García et al, 2013; Mercuri et al, 2022; Nicoll, 2004; Ritchie and Haynes, 1987). In arid lands, scholars documented the occurrence, within in the geological record, of pedosedimentary features that are incompatible with present-day dryland climates and environs (Cremaschi et al, 2010; Nicoll et al, 2021). Because such natural contexts were often found intimately mixed with archaeological remains, it quickly became clear that the very nature of human settlements, migrations and achievements throughout the archaeological past needed to be – at least partially – scrutinized through the lens of physical geography and environmental changes (Butzer, 1982; Heitz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Geoarchaeology-the practice of using techniques rooted in the geosciences to address archaeological research questions-has long-established foci on site-formation processes, geochronology, and the reconstruction of paleoenvironmental contexts as objects of scholarly investigation (e.g., Courty et al 1989, Goldberg & Macphail 2006, Nicoll et al 2021, Rapp & Hill 2006, Waters 1992. Such topics of inquiry have been so fundamental to the specialty that some scholars have suggested that all archaeology is essentially "geoarchaeology," given the degree to which any archaeological interpretation is premised on assumptions or explicit inferences about the formation and preservation of the excavated archaeological record (cf.…”
Section: Introductionmentioning
confidence: 99%